Model of Bus and Urban Rail Transfer Behavior Based on General Cost Function - Jielin Zhang; Tiezhu Li (Advances in Mechanical Engineering, 2015)
To design an efficient feeder bus route network and develop a better integrated intermodal system, it is necessary to study travelers' mode choice behavior. This paper focuses on the transfer behavior model between bus transit and urban rail. Based on the theory of Binary logit (BL) model, a new generalized travel cost model (GTC) which considers the influencing factors including travel distance, travel cost, and transfer time is established, and the choice model of bus and urban rail with the influence of transfer behavior is built. Then, a deeper analyzing process is conducted to get the significance of the model. In addition, the accuracy and feasibility of the model are verified through using the real survey data. Finally, according to the model results, some countermeasures consisting of improving the transfer condition and optimizing price charging pattern are given to promote a better public transportation system.